Cercetări de suprafață în așezări de la sfârșitul Epocii Bronzului și începutul Epocii Fierului din comuna Cozmești, jud. Iași. Rezultate preliminare - Casandra Brașoveanu; Alexandru Berzovan; Ștefan Honcu (Analele Banatului. Arheologie-Istorie, 2020)
Fieldwork is an important segment of archaeological research, contributing to the better knowing and understanding of different historical periods. Publishing the results obtained and the archaeological materials discovered after such an initiative can complete the image already formed about the communities that lived in the past. In the present study we tried to highlight some settlements belonging to the Late Bronze Age and Early Iron Age, some of which were not previously known in the literature. This time frame, although rich when talking about the discovery of settlements, was very little researched in the space that was proposed for studying. The last diggings that took place in archaeological sites belonging to this period can be placed a few decades ago. Thus, publishing the results of the field research carried out can represent an important starting point in the resumption of the archaeological research dedicated to this chronological sequence. This paper proposes a discussion on some archaeological materials specific to Noua and Corlăteni-Chișinău cultures, discovered in the settlements identified on the territory of Cozmești, Iași County. The spatial analysis of the three archaeological sites indicates the apartanence to the already-known pattern specific to the above-mentioned cultures. Noua communities are known to be interested in the geographical areas placed at the confluence of two rivers, with low and medium altitudes and smooth slopes, this fact being proven once again by the preferences manifested for the three settlements discussed here.